2019
DOI: 10.1016/j.ajhg.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Functional Interrogation of Genes in GWAS Loci Identified ATF1 as a Key Driver in Colorectal Cancer Modulated by a Promoter-Enhancer Interaction

Abstract: Genome-wide association studies (GWASs) have identified approximately 100 colorectal cancer (CRC) risk loci. However, the causal genes in these loci have not been systematically interrogated. We conducted a high-throughput RNA-interference functional screen to identify the genes essential for proliferation in the CRC risk loci of Asian populations. We found that ATF1, located in the 12q13.12 region, functions as an oncogene that facilitates cell proliferation; ATF1 has the most significant effect of the identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Such protective role could also be seen in other cancer types, such as colorectal cancer [34], gastric cancer [54], and esophageal cancer [55]. Other genetic, environmental factors, and gene-environment interaction may cooperatively determine the protective role of miR-34b/c rs4938723 T>C in neuroblastoma risk [56, 57].…”
Section: Discussionmentioning
confidence: 99%
“…Such protective role could also be seen in other cancer types, such as colorectal cancer [34], gastric cancer [54], and esophageal cancer [55]. Other genetic, environmental factors, and gene-environment interaction may cooperatively determine the protective role of miR-34b/c rs4938723 T>C in neuroblastoma risk [56, 57].…”
Section: Discussionmentioning
confidence: 99%
“…To gain insight into the potential functions of our identified SNPs and their related variants (r 2 ≥ 0.6), several public-available databases, including Haplo Reg v4.1 (https://pubs.broadinstitute.org/mammals /haploreg/), ENCODE, rSNPBase (http://rsnp.psych .ac.cn/index.do) [17,18], SNP2TFBS (https://ccg.epfl. ch/snp2tfbs/) [19], PINES (http://genetics.bwh.harv ard.edu/pines/index.html) and RegulomeDB (http: //regulome.stanford.edu/) [20], were used for functional annotations.…”
Section: Functional Annotations Pathway and Gene Ontology (Go) Analysesmentioning
confidence: 99%
“…The genotyping in the discovery stage was using the Illumina HumanExome Bead Chip and was reported before. 18 We phased the haplotypes with segmented haplotype estimation and imputation tool 20 and performed a genome-wide imputation with IMPUTE2 software, 21 based on the linkage disequilibrium and haplotypes information from the 1,000 Genomes Project Phase 3 Asian samples as references. A total of 69 poorly imputed variants with an information measure <0.40 were excluded from subsequent analyses (Fig.…”
Section: Snp Selection and Quality Controlmentioning
confidence: 99%
“…The principal components of genetic ancestry have been analyzed in the previous study and the results showed that there was no significant population stratification for the participants in the discovery stage. 18 Written informed consent was obtained from each subject at recruitment, and our study was approved by the Chinese Academy of Medical Sciences Cancer Institute and Institutional Review Board of Tongji Medical College, Huazhong University of Science and Technology.…”
Section: Study Subjectsmentioning
confidence: 99%